THE INFLUENCE OF HEALTH EDUCATION WITH A THINK PAIR SHARE LEARNING MODEL ON THE KNOWLEDGE AND ATTITUDES OF SCHOOL-AGE CHILDREN IN VEGETABLE CONSUMPTION - Sri Puasti Ningsih (Jurnal EduHealth, 2020)
The school-age group of children needs to get the fulfillment of the adequacy of its main nutrients with vegetable consumption. In fact, children still find it difficult to consume vegetables in adequate quantities. The think pair share method makes children will try to think, respond to each other and help in discussions. The aim of the study was to analyze the effect of the application of health education with a think pair share learning model on the knowledge and attitudes of school-age children in vegetable consumption.The study used pre-experimental research design (one-group pre-post testdesign). The population in this research is a grade IV student at SDI KHM Noer Surabaya. Sampling with total sampling technique. Respondents in this study numbered 40 respondents. The independent variable in the study was health education with a think pair sharelearningmodel. The dependent variables in the study are knowledge and attitude. Data collection using questionnaires. The data was analyzed using the Wilcoxon Sign Rank Test statistical test for knowledge and attitudes with significance α≤0.05.The results of the Wilcoxon Sign Rank Test show that health education with a think pair share learning model can affecta child's knowledge (p=0.000) and attitude (p=0.000).The results of this study concluded that health education with a think pair share learning model can increase children's knowledge and attitudes in vegetable consumption. Further research is expected to be conducted on the action of vegetable consumption in children with a multivariate statistical approach.